Preservative effect of coriander essential oil applied in different proportions on the storage of rainbow trout (Oncorhynchus mykiss) fillets - Kuzgun, Nermin Karaton; Sonmez, Pinar Erecevit; Tanyildizi, Muhammet Saban (Mattioli 1885, 2020)
Aim of this study, the sensorial, microbiological, and chemical features during shelf life at 2 +/- 2 degrees C of rainbow trout fillets samples treatment with coriander essential oils were examined of protective effect of oils. According to the findings of the research, the storage during of fillets ended on day 9th, that of control on day 12th, that of samples applied with coriander oils 0.1% on day 15th, which of fillets applied with coriander oils 0.25% and applied with coriander oils 0.5% on day 18th. The minimum number of bacteria, values of TVB-N and TBA were founded in trout fillets treatment with 0.5% coriander essential oil. In terms of the sensory quality of the fillets, as assessed by panelists participating in the panel, it was detected that highest point was given to the fillets groups to which coriander essential oil of 0.5% had been enforced, and as a result, with this application, it was underlined that was obtained in a positive direction of a flavor very different other than ordinary fish flavor by panelists.
Keywords: Coriander essential oil; rainbow trout; storage; microbiological quality; chemical quality